Robust control of a UPFC system with H control technique - Maamar Benyamina; Mohamed Bouhamida; Tayeb Allaoui; Rachid Taleb; Mouloud Denai (Institute of Advanced Engineering and Science, 2020)
FACTS (Flexible AC Transmission Systems) technology has now been accepted as a potential solution to the stability problem and load flow. The Unified Power Flow Controller (UPFC) is considered to be the most powerful and versatile among all FACTS devices. This paper presents the control of a UPFC system using Hinf robust control technique. A simulation study using Matlab/Simulink is presented to the performance of this control strategy and the robustness with respect to variations of the system parameters such as the inductance of the transmission line.